A systematic review of facial emotion recognition in Alzheimer’s disease:A developmental and gender perspective - Fernández Ríos, Mercedes; Redolat, Rosa; Serra, Emilia; González-Alcaide, Gregorio (Anales de Psicología / Annals of Psychology, 2021)
The correct identification of basic emotions (joy, fear, disgust, sadness, surprise and anger) plays an important role in social relationships and behaviors linked to one´s survival. In Alzheimer´s disease (AD) the ability to recognize emotions may already be impaired at early stages of the disease. Therefore, the main objective of the present study was to carry out a systematic review of the literature on facial emotional recognition in people with AD, identifying possible modulating variables. A search in the Web of Science and PsycInfo databases was carried out. After applying the inclusion-exclusion criteria, a total of 28 articles were selected. Static images were the most used stimuli to evaluate the recognition of basic emotions, especially the photographs developed by Paul Ekman and collaborators. Results of the present review indicate the people with AD generally display deficits in emotional recognition although the data are not conclusive, which could be related to the diversity of methodologies applied. In relation to the variables evaluated (sex and age) the need of further research in order to study how these factors could modulate emotional recognition in patients with Alzheimer´s disease is highlighted.